Criticism of legal positivism through Judge Angelo in the Shakespearean play "Measure for Measure" (International Seven Journal of Multidisciplinary, 2023)
This work seeks, through the use of the tool of Law and Literature, to explain the criticism of several theorists of legal positivism, in particular, the studies of Ronald Dworkin. For this, the work elaborated by Shakespeare “Measure for Measure” will be analyzed, which demonstrates in a very clear way all the critical notes in which legal positivism is involved. Through its main character, Judge Ângelo, it will be demonstrated when a judge acts in an exegetical way, that is, he mechanically fulfills the sayings of the laws, and when they start to decide in a way endowed with greater discretion, in which many Sometimes they act in this way to meet desires and understandings that they see as merely personal. Still, the present study seeks to understand the positivist approach to decision making, so that the criticisms that both Dworkin, Hart and Kelsen make to the subject are demonstrated. The present study took place through a qualitative and descriptive approach, with bibliographic research in legal journals, articles and books.